Prospective Observational Study to Assess Effectiveness and Safety of Intravenous Ferric Carboxymaltose 1000 mg in Patients of Chronic Heart Failure with Iron DeficiEncy - PRIDE-HF Study - Raghuraman, Bagirath; Jain, Rajendra Kumar; Badani, Rajesh Surendra; Patil, Sachin Narendra; Suares, Nanette; Dabhade, Dhammdeep; Shewale, Rishikesh; Suryawanshi, Sachin; G, Vikneswaran (Cardiology and Cardiovascular Medicine, 2023)
Objectives: The present study aims to assess the effectiveness and safety profile of intravenous (IV) ferric carboxymaltose (FCM) administration in patients with chronic heart failure (HF) having iron deficiency (ID) in real-world clinical practice. Methods: This was a prospective, multi-center, non-interventional, observational study that included patients aged 18 years and above of either gender. The included patients belonged to New York Heart Association (NYHA) class II – III who had ID. The primary objective of the study was to evaluate the effectiveness of treatment with injection FCM in patients of chronic HF with ID by assessing improvement in the symptoms at week 12. The study was registered with clinical trial registry of India (CTRI) [CTRI/2021/02/031307]. Results: A total of 98 subjects were enrolled in the study from 4 centers. The mean age of the study population was 61.08 ± 12.95 years with 58% being male. Primary endpoint of the study was a change in patients' symptoms assessed using NYHA class. There was a significant improvement in NYHA class from baseline to 12 weeks, with 56.1% of patients belonging to NYHA Class III as compared to only 8.4% at 12 weeks (P value < 0.001). No adverse events or hospitalizations were reported during the study period. Conclusion: Rectifying ID in chronic HF using IV FCM leads to substantial improvement in disease symptoms and haematological parameters which in turn may lead to favourable disease outcomes and lessen HF-related hospitalization. The study highlights IV FCM's potential as a promising therapy in HF management.